Synchronous genetic turnovers across Western Eurasia in Late Pleistocene collared lemmings. (25th February 2016) - Palkopoulou, Eleftheria; Baca, Mateusz; Abramson, Natalia I.; Sablin, Mikhail; Socha, Paweł; Nadachowski, Adam; Prost, Stefan; Germonpré, Mietje; Kosintsev, Pavel; Smirnov, Nickolay G.; Vartanyan, Sergey; Ponomarev, Dmitry; et al.
Abstract: Recent palaeogenetic studies indicate a highly dynamic history in collared lemmings ( Dicrostonyx spp.), with several demographical changes linked to climatic fluctuations that took place during the last glaciation. At the western range margin of D. torquatus, these changes were characterized by a series of local extinctions and recolonizations. However, it is unclear whether this pattern represents a local phenomenon, possibly driven by ecological edge effects, or a global phenomenon that took place across large geographical scales. To address this, we explored the palaeogenetic history of the collared lemming using a next‐generation sequencing approach for pooled mitochondrial DNA amplicons. Sequences were obtained from over 300 fossil remains sampled across Eurasia and two sites in North America. We identified five mitochondrial lineages of D. torquatus that succeeded each other through time across Europe and western Russia, indicating a history of repeated population extinctions and recolonizations, most likely from eastern Russia, during the last 50 000 years. The observation of repeated extinctions across such a vast geographical range indicates large‐scale changes in the steppe‐tundra environment in western Eurasia during the last glaciation. All Holocene samples, from across the species' entire range, belonged to only one of the five mitochondrial lineages. Thus, extant D. torquatus populations only harbour a small fraction of the total genetic diversity that existed across different stages of the Late Pleistocene. In North American samples, haplotypes belonging to both D. groenlandicus and D. richardsoni were recovered from a Late Pleistocene site in south‐western Canada. This suggests that D. groenlandicus had a more southern and D. richardsoni a more northern glacial distribution than previously thought. This study provides significant insights into the population dynamics of a small mammal at a large geographical scale and reveals a rather complex demographical history, which could have had bottom‐up effects in the Late Pleistocene steppe‐tundra ecosystem.